2011
DOI: 10.1111/j.1600-0609.2011.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Bulky disease has an impact on outcomes in primary diffuse large B-cell lymphoma of the breast: a retrospective analysis at a single institution

Abstract: Patients with bulky disease had a poorer prognosis and recurred frequently in the CNS. CNS prophylaxis might yield better outcomes, but a larger, prospective trial is needed to elucidate the optimal initial treatment of PBL in the rituximab era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
4
21
2
Order By: Relevance
“…[1,3,4,7,17,18,23] However, in line with the present study, there are studies reporting patients' age comparable to our cohort. [5,8,21,24] Some scattered reports suggested that younger patients more often had breast Burkitt's lymphoma which tended to involve bilateral breasts.…”
Section: Discussionsupporting
confidence: 90%
“…[1,3,4,7,17,18,23] However, in line with the present study, there are studies reporting patients' age comparable to our cohort. [5,8,21,24] Some scattered reports suggested that younger patients more often had breast Burkitt's lymphoma which tended to involve bilateral breasts.…”
Section: Discussionsupporting
confidence: 90%
“…As a rare subentity of DLBCL, PB‐DLBCL has been shown to display characteristic patterns of relapse distinct from those of nodal DLBCL . Particularly, a high frequency of extranodal relapses in the breast and CNS has been reported in previous studies . However, due to the rarity of this disease, the current published reports on PB‐DLBCL comprise predominantly small retrospective series, with only a few large cohort studies reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Further, identifying a higher risk subset would be useful but difficult given the rarity of the disease. There are anecdotal data that suggest bilateral involvement [48] and tumor size >5 cm [49] [50]. Therefore, patients with breast involvement appear to be at additional risk of CNS progression, and we recommend consideration of CNS-directed prophylaxis, particularly in the presence of one or more potential additional risk factors (stage IIE, stage-modified IPI score >2, bilateral involvement, or tumor size >5 cm).…”
Section: Breastmentioning
confidence: 98%